Magnetic immobilized enzymes microreactors for in-vitro metabolism assays and/or biocatalysis applications - Furlani, Izadora Liranço (2023)
Cytochrome P450s are a superfamily of hemeproteins widely used to study phase I reactions in in vitro drug metabolism assays and to correlate them with in vivo outcomes. In addition, this class of enzymes can be involved in the biosynthesis of high-value complex compounds and thus, has emerged as a key asset within industrial interest. Reactions catalyzed by CYPs are complex and routinely involve several steps. Moreover, problems related to the lack of catalytic activity and the constant supply of the cofactor nicotinamide adenine dinucleotide phosphate (NADPH) are some drawbacks to be overcome. Considering these aspects, new analytical alternatives should be implemented to transform conventional assays using CYP into a more valuable approach. Enzyme immobilization has been used for several years and it still represents a clever strategy to increase catalytic activity, stability, and when possible, to provide the reuse of the immobilized target. To meet this end, as the first part of the work herein described, the enzyme glucose-6-phosphate dehydrogenase (G6PDH) was covalently immobilized onto magnetic beads (G6PDH-Mbs). An LC-UV method was developed and qualified to quantify the production of NADPH. The biocatalyst bioreactor G6PDH-Mbs was characterized through kinetic studies where a sigmoidal profile was obtained. The application of G6PDH-Mb was demonstrated in in vitro metabolism assays using albendazole and fiscalin B. The implementation of G6PDH-Mb as a generator system increased 3-folds the production of the metabolites when compared to the use of commercial NADPH. The second part of the work is related to CYP immobilization. For that, rat liver microsomes (RLM) were used as a cost-effective alternative to modulating the immobilization conditions for CYP onto magnetic beads. Next, the optimized immobilization procedure was applied to human liver microsomal (HLM) to produce the biocatalytic bioreactor HLM-Mbs. Biotransformation reactions using HLM-Mbs were tested by monitoring the biotransformation of albendazole (ABZ) into albendazole-sulfoxide (ABZ-SO), and the temperature was evaluated to increase the production of the metabolites and the reuse of HLM-Mbs in multiple cycles. The application of HLM-Mbs in in vitro metabolism assays was demonstrated by kinetic and inhibition studies. In addition, catalytic activities for CYP2C9 and CYP2D6 were tested by evaluating the hydroxylation reactions of diclofenac and bufuralol as substrates. As a final contribution of this work, a dual biocatalyst bioreactor (G6PDH-HLM-Mbs) was created by mixing the generator system of NADPH (G6PDH-Mbs) with HLM-Mbs.